2007
DOI: 10.1016/j.peptides.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Peptide stabilized amphotericin B nanodisks

Abstract: Nanometer scale apolipoprotein A-I stabilized phospholipid disk complexes (nanodisks; ND) have been formulated with the polyene antibiotic amphotericin B (AMB). The present studies were designed to evaluate if a peptide can substitute for the function of the apolipoprotein component of ND with respect to particle formation and stability. An 18-residue synthetic amphipathic α-helical, solubilized vesicles comprised of egg phosphatidylcholine (egg PC), dipentadecanoyl PC or dimyristoylphosphatidylcholine (DMPC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Immunoblot analysis of a portion of selected column fractions revealed that Wnt3a and apoA-I co-elute from the column with an apparent molecular weight in the range of 100 kDa. This value is consistent with previous studies of ND [17, 2325] wherein evidence of discoidal morphology was obtained by electron microscopy or atomic force microscopy. By contrast, when a control sample containing apoA-I and Wnt3a, but no phospholipid, was chromatographed, apoA-I was recovered in the column eluate but Wnt3a was lost (data not shown).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…Immunoblot analysis of a portion of selected column fractions revealed that Wnt3a and apoA-I co-elute from the column with an apparent molecular weight in the range of 100 kDa. This value is consistent with previous studies of ND [17, 2325] wherein evidence of discoidal morphology was obtained by electron microscopy or atomic force microscopy. By contrast, when a control sample containing apoA-I and Wnt3a, but no phospholipid, was chromatographed, apoA-I was recovered in the column eluate but Wnt3a was lost (data not shown).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…18 Previous studies have shown that a truncated fragment of apolipoprotein and their oligomers can form a nanodisc by the interaction with lipids. 1923 Additionally, some amphipathic α -helical peptides have been found to form nanodiscs. 24,25 These facts suggested that an amphipathic structure of these proteins and peptides is essential to form lipid nanodiscs.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies will be required to evaluate ATRA-ND as an in vivo delivery vehicle for this potent inducer of cell differentiation and apoptosis. Since ND particles containing amphotericn B have been generated using apoliprotein A-I (Oda et al, 2006) or a synthetic amphipathic peptide (Tufteland et al, 2007), it is anticipated that ATRA-ND can be generated that contain one of several potential alternate scaffold proteins / peptides.…”
Section: Cell Viability Assaysmentioning
confidence: 99%